Fin-Tech Moderator Role in Attracting Foreign Direct Investments and Economic Growth - Mgadmi, Nidhal; Souid, Sahar; Moussa, Wajdi; Rachdi, Houssem (Journal of Telecommunications and the Digital Economy, 2025)
This study examines the moderating role of financial technology (Fin-Tech) in the attractiveness of foreign direct investment (FDI) and its impact in stimulating economic growth, with a particular focus on financial inclusion. The results reveal that in developed countries, various macroeconomic, institutional and Fin-Tech-related indicators have positive and statistically significant impacts on economic growth. Additionally, the quality of regulations and political stability are crucial determinants of FDI attractiveness in these countries. In contrast, variables such as interest rates and economic growth, measured by gross domestic product (GDP), do not demonstrate a significant contribution to FDI attractiveness. Furthermore, Fin-Tech technologies, such as digital payments and peer-to-peer lending (PPL), enhance FDI attractiveness, particularly when accompanied by robust institutional regulations and political stability. However, this effect diminishes in the presence of corruption controls. In developing countries, while most macroeconomic indicators have a positive influence on economic growth, the balance of payment deficit remains an outlier. The quality of regulation and use of digital payments also play significant roles, while PPL appears to have a negative effect. Finally, FDI in developing countries is more strongly influenced by factors such as population growth and institutional quality, especially regulatory quality and political stability.